2017
DOI: 10.1017/wet.2017.96
|View full text |Cite
|
Sign up to set email alerts
|

Dicamba-Tolerant Soybean Combined Cover Crop to Control Palmer amaranth

Abstract: A study was conducted to evaluate the response of glyphosate- and dicamba-tolerant (GDT) soybean and weed control from cover crop different termination intervals before and after soybean planting. Cover crop biomass was highest when terminated at planting, decreased with the 7- and 14-d preplant (DPP) and day-after-planting (DAP) timings, and again at the 14 DPP and DAP timings. Glyphosate+dicamba provided total control of cover crops by 21 DAP. Cover crop termination timing did not influence soybean populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Resistance will evolve independently in fields that continue to have intensive selection pressure from PPO inhibitors. Many are advocating alternative and integrated management methods 61–63 that include as many nonchemical approaches as possible 64,65 …”
Section: Resultsmentioning
confidence: 99%
“…Resistance will evolve independently in fields that continue to have intensive selection pressure from PPO inhibitors. Many are advocating alternative and integrated management methods 61–63 that include as many nonchemical approaches as possible 64,65 …”
Section: Resultsmentioning
confidence: 99%
“…Our results do not provide supporting evidence that surface residue mulch reduced herbicide efficacy or cash crop yields. Recent studies in corn and soybean production regions of the Midwest and Midsouth support the inference that herbicide inputs are the primary driver of cash crop yields and weed control performance, including multiple herbicide-resistant Amaranthus spp., when cover crops are integrated as a component of an IWM strategy (Loux et al 2017;Montgomery et al 2018;Wiggins et al 2015).…”
Section: Weed Control and Yield Performance Targetsmentioning
confidence: 99%
“…Recent studies have demonstrated that integrating cover crops can increase suppression of glyphosateresistant weeds, including fall-and spring-emerging horseweed [Conyza canadensis (L.) Cronquist] (Cholette et al 2018;Pittman et al 2019;Wallace et al 2019) and summer annuals Palmer amaranth (Amaranthus palmeri S. Watson) and waterhemp [Amaranthus tuberculatus (Moq.) Sauer] (Loux et al 2017;Montgomery et al 2018;Wiggins et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…First, recent studies have consistently demonstrated that integrating cover crops into annual grain crop rotations can improve suppression of current glyphosate-resistant weeds, including horseweed (Erigeron canadensis L.; Cholette et al 2018) and Amaranthus spp. (Loux et al 2017;Montgomery et al 2018;Wiggins et al 2016). And second, cover crops are increasingly integrated into annual grain crop rotations to provide multiple ecosystem services, including improved soil quality, maintenance of nutrient and water cycling, and enhanced biotic pest regulation (Wayman et al 2016).…”
Section: Introductionmentioning
confidence: 99%